Insentif PMK 86/2020 Di Tengah Pandemi Covid 19: Apakah Mempengaruhi Kepatuhan Wajib Pajak UMKM Di Surabaya? - Richard Andrew; Dian Purnama Sari (ITB AAS INDONESIA, 2021)
This study describes research Taxpayer Compliance in the Covid-19 pandemic. The purpose was to analyze and determine effects of socialization PMK 86/2020 incentives, tax rates, tax services, PP 23/2018 deadline, and tax punishment for MSME taxpayer compliance in Surabaya. The method in the research is quantitative by testing hypothesis. Data obtained through any questions and distributed via google form to all taxpayers (MSMEs) in the Surabaya.The results showed that variable of PMK 86/2020 incentive socialization, tax rates, tax services, deadline of PP 23/2018 has effects, while tax punishment hasn’t effect for MSME taxpayer compliance. The Conclusions are socialization of PMK 86/2020 incentives has been carried out by the government massively and they raises knowledge to immediately take advantage of incentives. They will to take advantage of lower tax rates during pandemic. The change in services from face-to-face to 100% online makes them easier to know information, procedures for compliance and keep health protocols in the pandemic. Deadline for PP 23/2018 supports them to understand how to bookkeeping until limit is given and utilization of determined rates. Tax punishment hasn’t effect because it’s not too strict during the pandemic and tend to be loose and various relaxation provided by the government.